Hubungan Sikap dan Pengetahuan Pedagang dengan Penggunaan Formalin dalam Ikan Asin Klotok yang Dijual di Pasar Tradisional Daerah Surabaya Utara - Kharisma Diva Arrahmah Casta Dienningrum (Media Gizi Kesmas, 2023)
Background: The misuse of formalin as an additive in food has been widespread especially in salted fish products. Formalin which is a dangerous chemical is used by salted fish producers so that their products are more durable and provide higher economic benefits. Objectives: The purpose of this study was to analyze the relationship between attitudes and knowledge of traders with the use of formalin in Klotok Salted Fish sold in traditional markets in North Surabaya. Methods: This research technique was analytic observational with a descriptive approach. Sampling was done ramdomly. The level of knowledge and attitudes of respondents were assessed through the result of the questionnaire. Formaldehyde testing was carried out using a formaldehyde test kit. The data were analyzed through the Fisher test Results: The result showed that there were Klotok Salted Fish containing formalin as much as 40 of the 41 samples. 10 respondents were in the good knowledge category, 19 respondents were in the medium knowledge category, and 12 respondents were in the low knowledge category. In the attitude assessment, there were 6 respondents who have a positive attitude, 32 respondents have a neutral attitude, and 3 respondents have a negative attitudes. Conclusions: There is no significant relationship (p>0.05) between the attitude and knowledge of traders with use of formalin in Klotok Salted Fizh sold in traditional markets in the North Surabaya.